2013
DOI: 10.1002/pip.2350
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive optical analysis of band gap profile, crystalline phase, and grain size for Cu(In,Ga)Se2 solar cells deposited by 1‐stage, 2‐stage, and 3‐stage co‐evaporation

Abstract: Cu(In,Ga)Se 2 (CIGS) thin films co-evaporated by 1-stage, 2-stage, and 3-stage processes have been studied by spectroscopic ellipsometry (SE). The disappearance of a Cu 2-x Se optical signature, detected by real time SE during multistage CIGS, has enabled precise endpoint control. Band gap energies determined by SE as depth averages show little process variation for fixed [Ga]/([In] + [Ga]) atomic ratio, whereas their broadening parameters decrease with increasing number of stages, identifying successive grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As a result, contactless metrologies that provide such information in real time are of great interest in this technology, especially for the development of ultrathin CIGS. We have demonstrated the use of RTSE for real-time monitoring and control of thin-film CIGS deposition [22]. Three sequential deposition processes are executed to obtain the final CIGS film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, contactless metrologies that provide such information in real time are of great interest in this technology, especially for the development of ultrathin CIGS. We have demonstrated the use of RTSE for real-time monitoring and control of thin-film CIGS deposition [22]. Three sequential deposition processes are executed to obtain the final CIGS film.…”
Section: Resultsmentioning
confidence: 99%
“…When the CIGS film becomes Cu rich, a semiliquid Cu 2 − x Se phase is believed to form on the bulk layer which consists of mixed phases of Cu(In,Ga)Se 2 and Cu 2 − x Se. Due to the presence of the semiliquid Cu 2−x Se phase, growth of large grains is known to occur [22]. During the third stage of deposition, the Cu-rich CIGS film is transformed into a Cu-poor film by the deposition of In, Ga, and Se.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in gallium signal intensity could be linked to the decrease in gallium concentration observed by both XRF and XRD. Changes in Ga profile in CIGS due to the fabrication process are known and have been observed when changing, for example, from a one-stage to a three-stage process [15], when modifying the copper content in the films [16] or when modifying the process temperature [17]. However, when designing intentionally the Ga profile, as in the three-stage process [12,17], one generally tries to have a Ga-rich layer at the back of the device (to form an electron back-reflector) and at the front of the device (to enhance open circuit voltage) while keeping the central part at a lower Ga content (to enhance current collection) [12,17].…”
Section: Post-deposition Recrystallization At 500 °Cmentioning
confidence: 99%
“…The one-step and three-step processes have been studied extensively, and the films prepared by each method have been compared to determine which process produces the better CIGS films. The differences in band gap profiles, crystalline phases, growth mechanisms, and element distributions between films prepared by the one-step and three-step processes are reported in the literature. These reports showed that the films made with the three-step process had a slightly better electrical performance than those made with the one-step process due to the films made with the three-step process having a Cu-poor surface, a double-graded band gap, good stoichiometry control, and a large-grained absorber. Notably, a small-area CIGS-type solar cell based on three-step co-evaporation was recently demonstrated to have an efficiency surpassing 20% in the laboratory, which is better performance than that exhibited by CIGS cells produced by other processes as well as that of conventional multicrystalline Si devices …”
Section: Introductionmentioning
confidence: 95%